The implementation of STE(A)M education through Scratch projects - Leshchuk, S; Dilna, N; Grod, I; Radchenko, O; Hnoiova, T (Journal of physics. Conference series, 2024)
The present research is motivated by the necessity of introducing modern methodologies corresponding to the study’s content into the educational process. The work aims to use Scratch projects for the organization of students’ educational activities, as well as for their creative self-realization. Authors realize STE(A)M-approach in the educational activity by facilities of Scratch-projects. The high-level block-based visual programming language could be an auxiliary technology for a teacher and an independent developing tool for students. The research revealed the main themes that became the basis for the development of the author’s course “Creative Self-Fulfilment in Scratch”. This contributes to the development of students’ creativity. The content of the course is extended with projects in algebra, geometry, physics and musical culture. Each of these projects demonstrates the unity of technology and creativity.